Penyalahgunaan Kombinasi Deksametason-Siproheptadin HCL sebagai Produk Peningkat Berat Badan dan Upaya Penegakan Hukumnya di Indonesia - Zwista Dimas Haryanto; Rossy Hertati; Ignatius Tutut Wahyanto; Rifki Rasyid (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
The misuse of the dexamethasone–cyproheptadine HCl combination as an illegal weight-gain product has become a serious public health concern in Indonesia due to its widespread availability and associated health risks. Although both drugs may stimulate appetite and promote weight gain, their use outside approved medical indications can lead to obesity, metabolic disorders, and psychological complications. This study aimed to describe the profile of illegal products, analyze distribution trends and geographic patterns, identify distribution modus operandi, and evaluate law enforcement efforts undertaken by the Indonesian Food and Drug Authority (BPOM). A mixed-methods approach was employed, combining quantitative analysis of BPOM cyber patrol data from 2023–2024 with a qualitative case study of Case Number 28/Pid.Sus/2025/PN Btl investigated by BPOM investigators in Yogyakarta. The results identified 2,641 online storefronts selling these illegal products in 2024, representing a substantial increase compared with 2023. The products were commonly repackaged in unlabeled or improperly labeled white bottles and were primarily distributed in Java, particularly in DKI Jakarta, West Java, and East Java. The main distribution modus operandi involved diverting prescription-only medicines from legitimate supply chains, followed by repackaging and online marketing. Although BPOM has enforced Law Number 17 of 2023 on Health against offenders, law enforcement remains constrained by relatively lenient judicial sanctions and challenges in tracing the original sources of diverted medicines. Strengthening distribution control, improving inter-agency coordination, and implementing an effective pharmaceutical traceability system are recommended to prevent diversion and protect public health.